2021
DOI: 10.3390/molecules26082398
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic Neurotransmission System Modulator, Vortioxetine, and Dopaminergic D2/D3 Receptor Agonist, Ropinirole, Attenuate Fibromyalgia-Like Symptoms in Mice

Abstract: Fibromyalgia is a disease characterized by lowered pain threshold, mood disorders, and decreased muscular strength. It results from a complex dysfunction of the nervous system and due to unknown etiology, its diagnosis, treatment, and prevention are a serious challenge for contemporary medicine. Impaired serotonergic and dopaminergic neurotransmission are regarded as key factors contributing to fibromyalgia. The present research assessed the effect of serotonergic and dopaminergic system modulators (vortioxeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 99 publications
0
11
0
2
Order By: Relevance
“…Recent researches revealed that VRT is also involved in the modulation of the glutamatergic and gammaaminobutyric acid (GABA)ergic neurotransmission in the specific brain regions [38]. Moreover, animal studies demonstrated the antinociceptive effects of VRT in sciatic nerve constriction [39] and oxaliplatin-induced neuropathy [40] or reserpine-induced fibromyalgia in mice [41]. Some researches proved the antinociceptive effects of carrageenan-induced paw inflammation in mice [42], but others noted the lack of influence of this antidepressant in the inflammatory neuropathic pain [39].…”
Section: Resultsmentioning
confidence: 99%
“…Recent researches revealed that VRT is also involved in the modulation of the glutamatergic and gammaaminobutyric acid (GABA)ergic neurotransmission in the specific brain regions [38]. Moreover, animal studies demonstrated the antinociceptive effects of VRT in sciatic nerve constriction [39] and oxaliplatin-induced neuropathy [40] or reserpine-induced fibromyalgia in mice [41]. Some researches proved the antinociceptive effects of carrageenan-induced paw inflammation in mice [42], but others noted the lack of influence of this antidepressant in the inflammatory neuropathic pain [39].…”
Section: Resultsmentioning
confidence: 99%
“…Учитывая способность АДР снижать неприятные ощущения в ногах при СБН, а также их антидепрессивный эффект, возник интерес к применению данной группы препаратов у пациентов с таким тяжелым аффективноболевым расстройством, как фибромиалгия. Она является заболеванием с низким порогом восприятия боли, аффективными расстройствами и мышечной слабостью [21]. В основе его лежит сложная дисфункция нервной системы без пускового фактора, что представляет серьезную проблему для диагностики, лечения и профилактики данного заболевания.…”
Section: терапия фибромиалгииunclassified
“…Исследование на мышах с химически индуцированными фибромиалгическими симптомами, вызванными подкожным введением резерпина, позволило оценить эффективность препаратов СИОЗС вортиоксетина и АДР ропинирола на болевой порог, выраженность депрессии и тревоги, а также двигательные нарушения. Внутрибрюшинное введение вортиоксетина и ропинирола в дозе 10 мг/кг купировало тактильную аллодинию, при этом ропинирол проявлял свойства, подобные антидепрессантам, а вортиоксетинподобные анксиолитикам, что можно учитывать при определении ведущих симптомов болезни [21,22]. Интересен тот факт, что в другом исследовании у пациентов с ИКР часто в анамнезе был диагноз фибромиалгии, что вновь возвращает к мысли о возможной генетической предрасположенности к развитию такого симптомокомплекса на фоне врожденных особенностей нейромедиаторной передачи [23].…”
Section: терапия фибромиалгииunclassified
“…Two main models of fibromyalgia-like conditions have been described to mimic altered, long-lasting, reflexive and nonreflexive pain-related behaviors [ 7 ]. In an experimental model of reserpine-induced myalgia (RIM3) with three injections of reserpine, the effect of various drugs has been tested in mice, including TRPV1 receptor antagonists [ 8 ], serotonin transporters inhibitors [ 9 ], bradykinin receptor antagonists [ 10 ], ligands of the nociceptin/orphanin FQ receptor [ 11 ], dopaminergic receptor agonists [ 12 ], toxins [ 13 , 14 , 15 ], gabapentinoids [ 14 ], resolvins [ 16 ], and plant-based polyphenol products [ 17 , 18 , 19 ]. In mice subjected to intramuscular injection of acidified saline solution (ASI), the effect of gabapentinoids [ 7 ] and plant-based polyphenol products [ 20 ] has also been tested.…”
Section: Introductionmentioning
confidence: 99%